Model Pembelajaran Blended Learning Tipe Rotasi Untuk Atlet Pelajar - Mulki Siti Hajar Rezaini; Yayat Ruhiat; Lukman Nulhakim (Postgraduate, University of Mataram, 2024)
Sports Education and Training Center is the main program organized by Ministry of Youth and Sports. This program focuses on developing student athletes at the secondary school level in various regions which includes a number of activities and is designed with the aim of improving student sports performance. The dual role of sports and academics that PPLOP student athletes have is a unique combination but has an impact on their learning achievements and is one of the problems that must be solved by schools. This research examines the readiness of schools to implement rotation-based Blended Learning for PPLOP student athletes at SMA Negeri 3 Serang Banten. This type of research is qualitative with a descriptive approach. The results of the research show that: Planning for the implementation of rotation type blended learning for PPLOP student athletes at SMAN 3 Serang Banten, Implementation of rotation type blended learning for PPLOP student athletes at SMAN 3 Serang Banten, Evaluation of the implementation of rotation type blended learning for student athletes at PPLOP